2020
DOI: 10.1186/s12879-020-05209-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal tuberculosis simulating a cancer-a case report

Abstract: Background: Tuberculosis is a disease that may affect any organ of the body. Multifocal tuberculosis involving multiple systems with associated symptoms are rare, which makes the diagnosis challenging. Distinguishing multifocal tuberculosis from lesions metastatic from system malignancy is difficult. Single detection method is difficult to make a diagnosis. A combination of multiple methods is essential. Case presentation: A 17-year-old male presented with a 20 days weakness of lower limbs, which aggravated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…4,5 However, FDG PET/CT image of tuberculosis in various sites may be misdiagnosed as malignant tumor. [6][7][8][9] Wang et al 10 reported a case of primary chest wall tuberculosis presenting as intense FDG uptake in the posterior pleural mass and adjacent muscle without rib involvement mimicking a malignancy. The patient in our case had simultaneous rib, muscle, and diaphragm invasion.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4,5 However, FDG PET/CT image of tuberculosis in various sites may be misdiagnosed as malignant tumor. [6][7][8][9] Wang et al 10 reported a case of primary chest wall tuberculosis presenting as intense FDG uptake in the posterior pleural mass and adjacent muscle without rib involvement mimicking a malignancy. The patient in our case had simultaneous rib, muscle, and diaphragm invasion.…”
Section: Figurementioning
confidence: 99%
“…FDG PET/CT has vital value in evaluating total disease burden and treatment response in tuberculosis patients 4,5 . However, FDG PET/CT image of tuberculosis in various sites may be misdiagnosed as malignant tumor 6–9 . Wang et al 10 reported a case of primary chest wall tuberculosis presenting as intense FDG uptake in the posterior pleural mass and adjacent muscle without rib involvement mimicking a malignancy.…”
mentioning
confidence: 99%
“…However, the results of 18 F-FDG PET/CT can be interpreted by malignancy or extrapulmonary tuberculosis. 1 FIGURE 2. 68 Ga-FAPI is a promising tracer for diagnostic imaging that is highly expressed in many malignant tumors.…”
mentioning
confidence: 99%
“…However, CT showed no obvious changes in the shape of the pancreas and no definite abnormality in other abdominal organs. However, the results of 18 F-FDG PET/CT can be interpreted by malignancy or extrapulmonary tuberculosis 1 …”
mentioning
confidence: 99%